A COMPARATIVE STUDY OF TYPES OF CONJUNCTIONS USED IN THE RESULTS AND DISCUSSION SECTION OF STUDENTS’ RAS AND TEFLIN JAs PUBLISHED IN 2015 - Dian Rahayu Purba; Safnil .; Rosnasari Pulungan (Universitas Bengkulu, 2017)
The purpose of this research was to identify the types of conjunctions used in students’ RAs (RAs) and TEFLIN journal articles (JAs). The design of this research was descriptive comparative method. The object of this study was 13 research articles written by S1 students of English Department of Education Faculty in University of Bengkulu graduated in 2015 and 2 TEFLIN journal articles which were published in 2015. The instrument used in this research was check-list and the data were collected by using documentation method. To analyze the data, the quantitative method, including statistical and descriptive analysis, was applied. The result of this research showed that the most common conjunction used in students’ RAs was and (42.98%) with subordinating conjunctions (61.74%) as the, while the most common conjunction used in TEFLIN JAs was that (36.66%). In addition, the most frequent type of conjunctions used in students’ RAs was coordinating conjunctions (56.11%), while the most frequent type of conjunctions used in TEFLIN JAs was subordinating conjunctions (61.74%). There was a significant difference between those two groups.